2019
DOI: 10.1096/fj.201900070r
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of GPR37 via regulation of inflammation and multiple cell death pathways after ischemic stroke in mice

Abstract: GPCR 37 (GPR37) is a GPCR expressed in the CNS; its physiological and pathophysiological functions are largely unknown. We tested the role of GPR37 in the ischemic brain of GPR37 knockout (KO) mice, exploring the idea that GPR37 might be protective against ischemic damage. In an ischemic stroke model, GPR37 KO mice exhibited increased infarction and cell death compared with wild‐type (WT) mice, measured by 2,3,5‐triphenyl‐2H‐tetrazolium chloride and TUNEL staining 24 h after stroke. Moreover, more severe funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 66 publications
(97 reference statements)
1
36
0
Order By: Relevance
“…In contrast, the detectable potential pro-inflammatory proteins MX2, SPP1 and PIBF1 were found to be down-regulated ( Figure 3 B, red), whereas the rather anti-inflammatory proteins ANXA1, LTBP1, SERPINA4 and TXN were found to be up-regulated in MB samples ( Figure 3 B, orange). Remarkable was the detection of a distinct molecular signature indicative for hypoxia, represented by the up-regulated proteins ADAMTS1 [ 38 ], GAP43 [ 39 ] and GPR37 [ 40 ] ( Figure 3 B, blue). The detailed classification of proteins is documented in Table S6 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the detectable potential pro-inflammatory proteins MX2, SPP1 and PIBF1 were found to be down-regulated ( Figure 3 B, red), whereas the rather anti-inflammatory proteins ANXA1, LTBP1, SERPINA4 and TXN were found to be up-regulated in MB samples ( Figure 3 B, orange). Remarkable was the detection of a distinct molecular signature indicative for hypoxia, represented by the up-regulated proteins ADAMTS1 [ 38 ], GAP43 [ 39 ] and GPR37 [ 40 ] ( Figure 3 B, blue). The detailed classification of proteins is documented in Table S6 .…”
Section: Resultsmentioning
confidence: 99%
“…In ischemic brain injury, autophagy is a double-edged sword and has controversial functions [28]. Increasing evidence suggests that increased autophagy acts as a detrimental mechanism in I/R injury [29,30,31,32,33]. Therefore, the modulation of autophagy could potentially aid in the prevention or the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings indicated that a reduction in Seipin expression disturbed autophagic flux and aggravated apoptosis in in PC12 cells. Long-lasting autophagy or impaired autophagic flux induces type II programmed cell death ( 53 - 55 ). It was previously observed that the knockdown of Seipin exacerbated cerebral I/R-induced damage in mice ( 26 ).…”
Section: Discussionmentioning
confidence: 99%